Analysis of aerosol-cloud-precipitation interactions based on MODIS data. Issue 1 (1st January 2017) - Cheng, Feng; Zhang, Jiahua; He, Junliang; Zha, Yong; Li, Qiannan; Li, Yunmei
Highlights: The indirect climate effect of aerosols in central-eastern China are studied. Four patterns of aerosol-cloud-precipitation interactions are proposed. The aerosol indirect effects have seasonal and regional differentiation. Abstract: Aerosols exert an indirect impact on climate change via its impact on clouds by altering its radiative and optical properties which, in turn, changes the process of precipitation. Over recent years how to study the indirect climate effect of aerosols has become an important research topic. In this study we attempted to understand the complex mutual interactions among aerosols, clouds and precipitation through analysis of the spatial correlation between aerosol optical depth (AOD), cloud effective radius (CER) and precipitation during 2000–2012 in central-eastern China that has one of the highest concentrations of aerosols globally. With the assistance of moderate resolution imaging spectroradiometer (MODIS)-derived aerosol and cloud product data, this analysis focuses on regional differentiation and seasonal variation of the correlation in which in situ observed precipitation was incorporated. On the basis of the achieved results, we proposed four patterns depicting the mutual interactions between aerosols, clouds and precipitation. They characterize the indirect effects of aerosols on the regional scale. These effects can be summarized as complex seasonal variations and north-south regional differentiation over the study area. The relationship between AOD and CER is predominated mostly by the first indirect effect (the negative correlation between AOD and CER) in the north of the study area in the winter and spring seasons, and over the entire study area in the summer season. The relationship between CER and precipitation is dominated chiefly by the second indirect effect (the positive correlation between CER and precipitation) in the northern area in summer and over the entire study area in autumn. It must be noted that aerosols are not the factor affecting clouds and rainfall singularly. It is the joint effect of aerosols with other factors such as atmospheric dynamics that governs the variation in clouds and rainfall.